Design, synthesis and evaluation of MCH receptor 1 antagonists—Part III: Discovery of pre-clinical development candidate BI 186908. Issue 16 (15th August 2015) - Oost, Thorsten; Heckel, Armin; Kley, Jörg T.; Lehmann, Thorsten; Müller, Stephan; Roth, Gerald J.; Rudolf, Klaus; Arndt, Kirsten; Budzinski, Ralph; Lenter, Martin; Lotz, Ralf R.H.; Maier, Gerd-Michael; et al.
Graphical abstract